Network Topology of Foreign Exchange Rate - Shamshuritawati, Sharif; Nur Syahidah, Yusoff; Maman Abdurachman, Djauhari (Canadian Center of Science and Education, 2012)
In this paper we use a network topology approach to examine the interrelationship of 55 world currencies which is based on correlation analysis. With this point of view, those relationships can be measured by a correlation structure among currencies. To analyse that network, we filter the important information contained therein by using minimum spanning tree, and we interpret it by using a centrality measures. This topology will gives us a useful guide to understand their behaviour and to determine the dominance currency in the network as part of a complex network. The results show that HKD-Hong Kong Dollar is the most dominance currencies, followed by in order of importance; SGD-Singapore Dollar, USD-US Dollar, SAR-Saudi Riyal, and TWD-New Taiwan Dollar.